2018
DOI: 10.1111/vox.12700
|View full text |Cite
|
Sign up to set email alerts
|

Applying newer parameter Ret‐He (reticulocyte haemoglobin equivalent) to assess latent iron deficiency (LID) in blood donors–study at a tertiary care hospital in India

Abstract: Ret-He can be used as a routine screening test to detect LID in blood donors. This could provide an opportunity to make appropriate and timely interventions like dietary changes or drug supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…37 Retic-Hb is reported to be a more reliable marker of iron restriction than sTfR in healthy blood donors. 38 An early indicator of response to iron therapy in IDA is provided by a rising Retic-Hb on day 4, 39 similar to the observation of a falling percentage of hypochromic red cells in response to therapy. 40 An algorithm for the diagnostic approach to IDA is suggested in figure 1.…”
Section: Guidelinesmentioning
confidence: 82%
“…37 Retic-Hb is reported to be a more reliable marker of iron restriction than sTfR in healthy blood donors. 38 An early indicator of response to iron therapy in IDA is provided by a rising Retic-Hb on day 4, 39 similar to the observation of a falling percentage of hypochromic red cells in response to therapy. 40 An algorithm for the diagnostic approach to IDA is suggested in figure 1.…”
Section: Guidelinesmentioning
confidence: 82%
“…Twari et al (13) demonstrated that RET-He might be a suitable marker for indicating latent iron deficiency in blood donors. Toki et al (9) found RET-He to be a useful marker in the diagnosis of overt iron deficiency anemia.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, the Ret-He has already been proposed as an additional marker to screen for ID [8,[11][12][13][14][15][16]. For example, Toki et al revealed that Ret-He may be associated with ID by a sensitivity of 92.0% and a specificity of 81.0% (area under the curve (AUC) = 0.902) using a Ret-He cut-off value of ≤30.9 pg in adults [17].…”
Section: Introductionmentioning
confidence: 99%